Reimagining literacy strategies in early childhood education of Indonesia: A systematic literature review - Yuanita Anis Isnaini; Avanti Vera Risti Pramudyani; Dwi Hastuti; Dewi Eko Wati (Universitas Ahmad Dahlan, 2025)
Early childhood literacy is a fundamental skill in developing language skills, critical thinking, communication, and understanding context. However, PISA results indicate that early childhood literacy in Indonesia remains low, while the literature synthesis on how literacy is implemented in contextual and sustainable early childhood education (PAUD) settings is very limited. Therefore, this study aims to analyze research trends in the application of literacy in the PAUD environment through a Systematic Literature Review (SLR) study using a modified SLR protocol. The main database used by Google Scholar involves 21 articles published between 2017 and 2025, and analyzed thematically. The findings show that implemented literacy in early childhood education of Indonesia includes reading, writing, and storytelling skills, it implies that the concept of literacy need to be expanded. Another finding is that parents play a role in building a culture of literacy. This study recommends for a broad mastery of literacy skills to create more appropriate literacy learning in Indonesian context. It also encourages teachers to develop children's literacy skill through more various attractive activities.